The Influence of Western Countries on (Turkey-Soviet Union) Relations in the Outbreak of World War II 1939 - Payman Abdullah Hamad; Bakhtyar Saaid Mahmood; Kaivan Shafei (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
In general, the political formulas on 1939, tend to be much complicated, at this time Turkey and Soviet Union where before they were to friendly countries, however, their relations took a negative direction caused by different factors, most importantly, the approach of Turkey to the Western countries, which was against what Stalin was looking forward. The reason was that the friendly relations between Turkey and Western countries directly impacted on fading of the relationships with the Soviet Union. This gap encouraged Germany so that Hitler can approach to his dreams and to use it for the reconstructing of world map, and to accomplish his goals he approached to the Soviet Union, regardless that he did not interest in Communism and signed an agreement with. This agreement negatively impacted on the relations with Turkey and get a way from each other. On the other hand, Turkey leaned to United Kingdom and France. As a result, each of them signed agreements against each other.